2018
DOI: 10.1007/s10570-018-2182-8
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-containing bioactive dressing for possible application in post-operative keloid therapy

Abstract: Bioactive dressing based on bacterial cellulose modified with carboxymethyl groups (mBC) was successfully prepared and studied. The surface of mBC was activated using carbodiimide chemistry and decorated with alginate/hydroxypropyl cellulose submicroparticles containing dexamethasone phosphate (DEX-P). Prior to their deposition particles were coated with chitosan in order to facilitate their binding to mBC, and to increase the control over the release process. The detailed physicochemical characterization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Current treatment approaches include topical anti-scarring application, surgical excision, cryotherapy, pressure dressing, laser therapy, intralesional corticosteroid injections, and antimetabolites. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The aim of this review is to briefly describe cutaneous wound healing processes and the participating immune cells, then provide a comprehensive overview of the immune and associated molecular targets involved in raised dermal scarring conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment approaches include topical anti-scarring application, surgical excision, cryotherapy, pressure dressing, laser therapy, intralesional corticosteroid injections, and antimetabolites. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The aim of this review is to briefly describe cutaneous wound healing processes and the participating immune cells, then provide a comprehensive overview of the immune and associated molecular targets involved in raised dermal scarring conditions.…”
Section: Introductionmentioning
confidence: 99%
“…ALG and HPC were used as the main components of the nanoparticles' matrix. We have used the same components previously to encapsulate other biologically active agents [21][22][23] and we have found that the ratio of both polymers must be adjusted individually to each active compound being delivered. In the case of PIO, due to its moderate solubility in water, a surfactant (Pluronic ® P103 or Tween ® 85) micelles were used to facilitate the encapsulation of PIO in the relatively hydrophilic ALG/HPC matrix.…”
Section: Resultsmentioning
confidence: 99%
“…To deposit chitosan-coated nanospheres on the surface of bacterial nanocellulose modified with carboxyl groups (mBNC), a procedure described and optimized in our previous work was applied [21]. A 4 cm 2 patch of mBNC was immersed in an acetate buffer (pH = 5.5) at room temperature.…”
Section: Deposition Of Np-pio/ch Particles On Modified Bacterial Nanomentioning
confidence: 99%
“…Another inexpensive and biocompatible CL derivative is hydroxypropyl cellulose. It was used as a component of bioactive dressing with corticosteroid dexamethasone as an active agent [ 151 ]. ALG and hydroxypropyl CL were applied for the drug encapsulation and crosslinked with calcium ions.…”
Section: Complexed Delivery Systemsmentioning
confidence: 99%